2021
DOI: 10.1021/acs.jpcc.0c11073
|View full text |Cite
|
Sign up to set email alerts
|

Trapping Mechanisms and Delayed Recombination Processes in Scintillating Ce-Doped Sol–Gel Silica Fibers

Abstract: The carrier trapping and recombination mechanisms occurring in Ce-doped silica fibers, produced by a sol−gel technique, are investigated by combining temperature-dependent steady-state X-ray-excited luminescence, wavelength-and timeresolved scintillation measurements, and wavelength-resolved thermally stimulated luminescence, focusing especially on the temperature range from 10 to 320 K. The scintillation decay features a decay time of the order of tens of nanoseconds, characteristic of the parity-and spin-all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 92 publications
(118 reference statements)
1
6
0
Order By: Relevance
“…The TSL intensity values have been corrected for the variation of the radioluminescence emission intensity vs. temperature to decouple the trap contribution to the emission from the other mechanisms involved in scintillation. The glow curve is broad and smooth, without any clear signal peak and reaches its maximum intensity at around 100 K. This featureless shape, without any narrow peak structure that marks a specific energy, suggests the existence of a broad energy distribution of trap states, 38,39 in agreement with the smooth radioluminescence and photoluminescence spectra that mirrors the presence of many different local environments and quenching pathways for the nanocrystal emitting ligands (Figure 2F). Notably, the TSL intensity is only a few percent (2.5%) of the total radioluminescence intensity (Supplementary Information), thus indicating that trapped energy has a minor contribution to the room temperature scintillation and does not seriously affect the material scintillation yield.…”
Section: Scintillation Properties Of Hf-dpa Nanocrystalssupporting
confidence: 58%
“…The TSL intensity values have been corrected for the variation of the radioluminescence emission intensity vs. temperature to decouple the trap contribution to the emission from the other mechanisms involved in scintillation. The glow curve is broad and smooth, without any clear signal peak and reaches its maximum intensity at around 100 K. This featureless shape, without any narrow peak structure that marks a specific energy, suggests the existence of a broad energy distribution of trap states, 38,39 in agreement with the smooth radioluminescence and photoluminescence spectra that mirrors the presence of many different local environments and quenching pathways for the nanocrystal emitting ligands (Figure 2F). Notably, the TSL intensity is only a few percent (2.5%) of the total radioluminescence intensity (Supplementary Information), thus indicating that trapped energy has a minor contribution to the room temperature scintillation and does not seriously affect the material scintillation yield.…”
Section: Scintillation Properties Of Hf-dpa Nanocrystalssupporting
confidence: 58%
“…52−58 The disambiguation of this dual effect of polyacrylates is particularly relevant for LHP-NCs based plastic scintillators because, under ionizing radiation excitation, defects in the NCs surfaces and/or at the NC/polymer interface could act as traps for the NCs excitons and for free charge carriers, resulting in low light yield, slow scintillation tails, and delayed recombination pathways detrimental to the scintillation performance. 59,60 In this work, we aim to contribute to the advancement of this field by investigating the scintillation properties of CsPbBr 3 NCs synthesized via LARP and the effect of their incorporation into PMMA nanocomposites. Our results fill a gap in the knowledge of the scintillation physics of LHP NCs and clarify the controversial role of the polyacrylate host in the scintillation properties.…”
mentioning
confidence: 99%
“…Indeed, another often largely overlooked critical aspect in the fabrication of nanocomposite scintillators is the effect of embedding on the scintillation properties and competing charge/exciton trapping mechanisms . Specifically, optical spectroscopy studies agree that the embedding in nonpolar polymers, such as polystyrene (PS), leaves the optical properties of LHP-NCs largely unaltered and enhances their stability against oxygen and moisture through a sealing effect. , Unfortunately, the mass polymerization of PS and its derivatives requires thermal polymerization approaches at high temperature (≥80 °C) that typically degrade the NCs and/or cause phase transitions to nonemissive allotropes. , On the other hand, polyacrylates, such as polymethyl methacrylate (PMMA), can be polymerized with less aggressive photoinitiated routes but their effect on LHP-NCs is still debated. , Specifically, studies showed the deterioration of the NC surfaces due to the partial polarity of the acrylic moieties, leading to a lower emission efficiency, , while others demonstrated the beneficial surface passivation of undercoordinated cation sites by the carboxylate-methacrylate units, leading to increased luminescence yield or photovoltaic performance. The disambiguation of this dual effect of polyacrylates is particularly relevant for LHP-NCs based plastic scintillators because, under ionizing radiation excitation, defects in the NCs surfaces and/or at the NC/polymer interface could act as traps for the NCs excitons and for free charge carriers, resulting in low light yield, slow scintillation tails, and delayed recombination pathways detrimental to the scintillation performance. , …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In Figure 4b, we report the spectrally‐integrated TSL signal as a function of temperature (the so‐called glow curve), which highlights the broad TSL signal (FWHM ≈90 K) centered at T = 170 K, suggesting the presence of a significantly large distribution of trap states. [ 36 ] To quantitatively determine the energy depth of the trap states responsible for the TSL signal, we performed a partial cleaning analysis and applied the initial rise method (see Supplementary Discussion 1, Supplementary Figure S8 for the calculation details), [ 37 ] which leads to an energy depth range spanning from 200 ± 12 to 370 ± 20 meV. It is also worth noting that, at any temperature, the TSL signal arose from the Sb‐centers, as highlighted in Figure 4c, showing essentially no modification in the recorded TSL spectra from T = 15 to 300 K, centered at ≈1.9 eV, and in very good agreement with the PL and RL spectra discussed above, further corroborating that the only emissive centers are the distorted [SbCl 6 ] 3− octahedra.…”
Section: Resultsmentioning
confidence: 99%